2004
DOI: 10.1016/s0377-1237(04)80057-1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Differentials of Hepatitis B Carrier State in the Army : A Community Based Sero-epidemiological Study

Abstract: The relatively high level of seroprevalence among recruits has led to certain recommendations on testing and further studies in specific groups, based on the findings of the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…9 A study conducted on Armed Forces population has found highly significant association of HBV positivity with having indulged in sex with CSWs and taking injections in civil set up. 4 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 A study conducted on Armed Forces population has found highly significant association of HBV positivity with having indulged in sex with CSWs and taking injections in civil set up. 4 …”
Section: Methodsmentioning
confidence: 99%
“…4,5 Hence there was a perceived need to undertake a study on an adequately large and representative sample of army personnel and their dependants, with a view to obtain a picture of frequency and distribution of HBV and HCV in the Armed Forces population.…”
Section: Introductionmentioning
confidence: 99%
“…18 One community-based study, however, found a seroprevalence rate of 7.9%. 19 While these data were surprisingly high, the sample size was relatively smaller (n = 1506) and it included personnel serving in the Army Medical Corps. Moreover, this study with an unusually high HBV prevalence was undertaken between 1997 and 1999.…”
Section: Hepatitis Bmentioning
confidence: 99%
“…However maximum sufferers with severe hepatitis sooner or later were recovering completely. In a few patients, the ailment turns into chronic and is referred to as chronic hepatitis [9]. Human beings with persistent hepatitis may also revel in mild, indistinct symptoms of fatigue and poor urge for food.…”
Section: Introductionmentioning
confidence: 99%